Fundamentals for Nursing : review module - Assessment Technologies Institute (s.l. : ATI, Assessment Technologies Institute)
This review module is a component of the Comprehensive Assessment and Review Program and is designed to be used in conjunction with content area exams. It includes key points and critical thinking exercises (with answer keys) for nursing management for a variety of conditions.
Includes bibliographical references (p. 568-571).
Keywords: Nursing -- Examinations, questions, etc; Nursing; Nursing Process; Nursing -- Outlines; Nursing -- Examinations, questions, etc